جماليات الخطاب السردي في رواية تراتيل أنثى لعلى عون الله - بن قدور, سليماني, صليحة دلال (University of El-oued, 2021)
إن دراستنا هذه تهدف إلى الكشف عن جماليات الخطاب السردي في رواية تراتيل أنثى لعلي عون الله، هي رواية جزائرية تحكي معاناة الأنثى وعلاقتها بالمجتمع، في هذه الدراسة نسعى إلى الكشف عن الجماليات التي وظفها الروائي، متبعين على المنهج السميائي، بداية من مدخل محددين فيه بعض المفاهيم من مفهوم الخطاب السرد الجمالية، وينقسم البحث إلى فصلين ويتسم الفصل الأول بعناصر السرد يندرج تحته الشخصية و الزمن و المكان، والفصل الثاني قد خصصناه لمكونات السرد من السارد المسرود المسرود له. وفي الأخير مجموعة من النتائج خاتمة لهذه الدراسة Abstract : Our study aims to reveal the aesthetics of the narrative discourse in the novel of female hymns by Ali Aoun Allah, which is an Algerian novel that tells the suffering of the female and its relationship to society. Concepts from the concept of aesthetic narrative discourse, and the research is divided into two chapters. The first chapter is characterized by the elements of narration, under which the personality, time and place fall, and the second chapter we have devoted to the components of the narration of the narrator listed to him Finally, a set of conclusions for this study
Keywords: الخطاب السرد الخطاب السردي